'A Saint for all Australians'?. (4th January 2016) - Laffin, Josephine
Abstract : On 17 October 2010 Mary MacKillop became the first Australian citizen to be officially canonized by the Roman Catholic Church. This event generated a similar outpouring of patriotic enthusiasm to that which greeted Mary's beatification in 1995. The title of this paper is borrowed from a newspaper article of 1985 by the poet, publisher and self-described 'implacable agnostic', Max Harris, a fervent supporter of Mary's canonization. Saints are the only relatives that you can choose, commented Bishop Ambrose of Milan in the fourth century, and taking this ancient aphorism rather more literally than St Ambrose intended, Dame Edna Everage has claimed descent from a branch of the MacKillop family tree. As Dame Edna's creator, comedian and satirist Barry Humphries, is a shrewd observer of Australian culture, Mary MacKillop's triumph as a saint for all Australians seems assured — but what does this reveal about the meaning of sainthood in contemporary Australian society? This paper will trace some important stages in devotion to saints in Australian history before returning to Mary Helen MacKillop, her status as a national icon, and the threads of change and continuity which can be discerned in her cult.